(untitled) (Indian Journal of Animal Production and Management, 2024)
The comprehensive integration of behavioural and functional traits in the selection and breeding of dairy cattle represents a holistic approach. The particular emphasis on behavioral traits, particularly milking temperament, holds significant importance for animal breeders. These traits not only exert a notable influence on production metrics but also contribute to the longevity of dairy animals. Consequently, these factors collectively impact the overall profitability and sustainability of dairy enterprises. While developed countries have embraced a holistic approach in their dairy cattle selection programs, the studies on milking temperament and milking speed of indigenous cattle in the Indian subcontinent remain limited. This review aims to present existing research on the genetic parameters of milking temperament and milking speed in dairy cattle, with a specific focus on the need for future strategies in studying these traits in Indian cattle. In light of research suggesting the pivotal role of good milking temperament and balanced milking speed for enhanced sustainability, it is imperative to establish a systematic recording system with a standardized scale specifically tailored for Indian cattle breeds. This initiative would contribute to the overall understanding and improvement of milking traits, fostering the development of more effective selection criteria.